GAMBARAN PERILAKU TERHADAP ROKOK PADA WARGA DI KELURAHAN SOKANANDI KABUPATEN BANJARNEGARA - Barni; Ratih Subekti (Jurnal Ilmiah Medsains, 2020)
Smoking is a dangerous form of bad behavior for health. Consumption Cigarettes can cause various diseases such as lung cancer, heart disease, narrowing of blood vessels and others. Amount smoker in Indonesia is increasing from year to year. The purpose of this study is to describe behavior to cigarettes on residents in Sokanandi Village, Banjarnegara Regency. This research is a descriptive research with cross sectional method. The research was carried out in Sokanandi Village, Banjarnegara Regency. Data collection was done with observation and interview techniques. Analysis of the data used is univariate analysis. Amount a sample of 30 respondents. The results obtained showed that some of the respondents did not smoke 86.7%, behaved avoiding cigarette smoke 63.3%, behaved reprimanding when disturbed by cigarette smoke, 73.3%, behaved reminding their families not to smoke 66.6%. Various the form of behavior towards smoking shows that more than half of the informants have implemented good behavior. Therefore, it is hoped that health agencies will continue to strengthen the campaign no smoking so that public awareness to avoid the dangers of smoking increases.